Analysis of the metabolic shift that accompanies differential activation of microglia - Holland, Robert (Trinity College (Dublin, Ireland). Department of Physiology, 2017)
Microglia, the resident immune cells of the central nervous system (CNS), adopt different phenotypes upon activation by different stimuli. The primary role of microglia is protection and maintenance of homeostasis, and any threat to homeostasis results in activation of cells. Under normal circumstances, cells switch back to their resting state once the threat is removed, but this ability to switch is decreased with age, whereupon cells become persistently activated. Dysfunctional, chronic activation of inflammatory microglia has been associated with most neurodegenerative disorders. In recent years, it had become evident that immune cell function and metabolism are intrinsically linked, with pro-inflammatory cells demonstrating increased glycolysis while anti-inflammatory cells are associated with increased oxidative metabolism. However, this metabolic reprogramming has not yet been investigated in the CNS. The aims of this study were to characterise microglial activation states in terms of their metabolic and iron handling profiles in vitro and to determine whether these changes accompany the inflammation that occurs in microglia in the brains of aged mice and APP/PSl mice.
Keywords: Physiology, Ph.D.; PhD Trinity College Dublin, 2017